A randomised controlled trial to assess the efficacy of dihydroartemisinin-piperaquine for the treatment of uncomplicated falciparum malaria in Peru - Grande, T; Bernasconi, A; Erhart, A; Gamboa, D; Casapia, M; Delgado, C; Torres, K; Fanello, C; Llanos-Cuentas, A; D'Alessandro, U (Public Library of Science, 2007)
Background Multi-drug resistant falciparum malaria is an important health problem in the Peruvian Amazon region. We carried out a randomised open label clinical trial comparing mefloquine-artesunate, the current first line treatment in this region, with dihydroartemisinin-piperaquine. Methods and Findings Between July 2003 and July 2005, 522 patients with P. falciparum uncomplicated malaria were recruited, randomized (260 with mefloquine-artesunate and 262 with dihydroartemisinin-piperaquine), treated and followed up for 63 days. PCR-adjusted adequate clinical and parasitological response, estimated by Kaplan Meier survival and Per Protocol analysis, was extremely high for both drugs (99.6% for mefloquine-artesunate and 98.4% and for dihydroartemisinin-piperaquine) (RR: 0.99, 95%CI [0.97−1.01], Fisher Exact p = 0.21). All recrudescences were late parasitological failures. Overall, gametocytes were cleared faster in the mefloquine-artesunate group (28 vs 35 days) and new gametocytes tended to appear more frequently in patients treated with dihydroartemisinin-piperaquine (day 7: 8 (3.6%) vs 2 (0.9%), RR: 3.84, 95%CI [0.82–17.87]). Adverse events such as anxiety and insomnia were significantly more frequent in the mefloquine-artesunate group, both in adults and children. Conclusion Dihydroartemisinin-piperaquine is as effective as mefloquine-artesunate in treating uncomplicated P. falciparum malaria but it is better tolerated and more affordable than mefloquine-artesunate (US$1.0 versus US$18.65 on the local market). Therefore, it should be considered as a potential candidate for the first line treatment of P.falciparum malaria in Peru.